2017
DOI: 10.1139/cjb-2016-0164
|View full text |Cite
|
Sign up to set email alerts
|

Life stages, demographic rates, and leaf damage for the round-leaved orchids,Platanthera orbiculata(Pursh.) Lindley andP. macrophylla(Goldie) P.M. Brown in a northern hardwood forest in New Hampshire, USA

Abstract: Life stages, demographic rates and leaf damage for the round-leaved orchids, Platanthera orbiculata (Pursh.) Lindley and P. macrophylla (Goldie) P.M. Brown in a northern hardwood forest, New Hampshire, USA. rates for a species pair of rare round-leaved orchids (Platanthera spp.) in a northern hardwood forest. Marked individuals were measured over five years, including: leaf area, damage by herbivores and pathogens, flowering and seed production. Germination trials were also conducted. Vital rates were very sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…The ericoid mycorrhizal community was mainly composed of three fungal genera (Rhyzoscyphus, Sebacinales, and Leptodontidum) that are known to colonize the roots of orchids (Nguyen et al, 2016). Cleavitt et al (2017) recently observed that two round-leaved orchid species ( Platanthera orbiculate and P. macrophylla ) at Hubbard Brook may be experiencing a population bottleneck evidenced by a higher proportion of orchids at adult-compared to juvenile life-stages as well as low juvenile survivorship. Seed establishment and juvenile survivorship of orchids during early mycoheterotrophic life-stages are known to be highly dependent on close association with the fungal symbiont (McCormick et al, 2018), and the results from our study suggest the distribution of these fungal symbionts will decline with future reductions in winter snow depth at Hubbard Brook.…”
Section: Discussionmentioning
confidence: 99%
“…The ericoid mycorrhizal community was mainly composed of three fungal genera (Rhyzoscyphus, Sebacinales, and Leptodontidum) that are known to colonize the roots of orchids (Nguyen et al, 2016). Cleavitt et al (2017) recently observed that two round-leaved orchid species ( Platanthera orbiculate and P. macrophylla ) at Hubbard Brook may be experiencing a population bottleneck evidenced by a higher proportion of orchids at adult-compared to juvenile life-stages as well as low juvenile survivorship. Seed establishment and juvenile survivorship of orchids during early mycoheterotrophic life-stages are known to be highly dependent on close association with the fungal symbiont (McCormick et al, 2018), and the results from our study suggest the distribution of these fungal symbionts will decline with future reductions in winter snow depth at Hubbard Brook.…”
Section: Discussionmentioning
confidence: 99%
“…Given the observed recent increase in loss of flowering individuals to deer herbivory (2016 onward), we were particularly interested in how much impact loss of flowering individuals would have on the two species demographic rates. Cleavitt et al (2016) reported P. orbiculata produced more flowers per spike and was more likely to flower consecutive years than P. macrophylla. Do these differences lead to more stable or growing populations for P. orbiculata?…”
Section: Introductionmentioning
confidence: 97%
“…We use the species pair of the round-leaved orchids, Platanthera macrophylla and P. orbiculata, to explore potential differences in their vulnerabilities to such looming environmental changes. Previous work on these orchids found critical thresholds for leaf area pertaining to both individual life stage transitions and survival (Cleavitt, Berry, Hautaniemi, & Fahey, 2016). Both species are forest dwelling, terrestrial orchids endemic to North America, and are variously listed as rare, threatened, endangered, or extirpated throughout parts of their range in Canada and the United States (NatureServe, 2015; USDA-NRCS, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Herbivory can greatly influence vegetation communities. Individual plant factors, such as species, life stage, nutrient quality, and defensive chemical potency [13][14][15][16], contribute to the extent of herbivore damage to plant communities. Community-level impacts, including floral dynamics [17,18], herbivory timing and intensity [19,20], and trophic interactions [21,22], also dictate the influence of herbivory.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of apex predators in the eastern U.S. has aided in the overabundance of primary consumers, specifically white-tailed deer (Odocoileus virginianus Zimmermann), a species noted for its impact on plant composition and structure in eastern U.S. ecosystems, including the biodiverse mixed-mesophytic forests of Appalachia [23]. Vulnerable plants, such as American ginseng (Panax quinquefolius L.) and several understory forbs, have experienced sharp declines in numbers and population viability as a result of increased deer browsing [14,24,25]. Areas with high deer densities commonly experience regenerating forests with compositions reflective of differences in plant species palatability and defensive mechanisms to reduce browsing; less palatable and more defensive plant species become more common in these areas, which dictates compositional and structural changes manifested with forest aging [26].…”
Section: Introductionmentioning
confidence: 99%